Retrospective analysis of accumulated structured practice: A Bayesian multilevel analysis of elite Brazilian volleyball players - Mendes, F. G.; Nascimento, J. V.; Souza, E. R.; Collet, C.; Milistetd, M.; Côté, J.; Carvalho, H. M. (High Ability Studies, 2018)
The patterns of cumulated structured volleyball practice and other structured sports activities of elite adult Brazilian players, considering age of specialization in volleyball and achievement of international competition representing the national team, were examined using Bayesian multilevel models. Elite volleyball players (n = 78) with an average age of 19.2 (SD = 0.9) years were considered. We used retrospective quantitative questionnaire to track individual training history. The mean age of specialization in volleyball was 10.7 (95% CI 10.3 to 11.0) for players that specialized early (before age 12), 14.1 (95% CI 13.9 to 14.3) for players that specialized intermediate (between ages 13 and 15), and 16.2 (95% CI 15.7 to 16.7) for players that specialized late (after age 16). Consequently, the earlier the specialization age in volleyball, the more years of training experience were accumulated. International and national level players were similar in both specialization age and pattern of engagement in other structured sport activities. Conditional on the data and models, attainment of expertise in volleyball may be favored by the accumulation of nonspecific sport experiences at early ages, and specialization may occur at a rather late age during adolescence.